2020
DOI: 10.1111/ppa.13188
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability of Polish tomato black ring virus isolates and their satellite RNAs

Abstract: Tomato black ring virus (TBRV), a member of the Nepovirus genus, is a serious plant pathogen distributed worldwide. It causes significant damage to several economically important crops, such as artichoke or strawberry. The TBRV bipartite genome consists of two polyadenylated single‐stranded positive‐sense RNA molecules, which may be accompanied by subviral particles such as defective interfering RNAs (DI RNAs) and satellite RNAs (satRNAs). In this study, we obtained the complete genome sequence of six TBRV iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
17
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 28 publications
5
17
0
Order By: Relevance
“…In previous studies to ours (Hemmer et al, 1987; Zarzyńska‐Nowak et al, 2020), satellite RNAs were found to be commonly associated with the genomes of TBRV and BRSV. The study by Zarzyńska‐Nowak et al (2020) working on TBRV isolated in Poland identified satellite RNAs in 8 of 10 isolates from a range of different plant species, finding them to be associated rather commonly.…”
Section: Discussionsupporting
confidence: 54%
“…In previous studies to ours (Hemmer et al, 1987; Zarzyńska‐Nowak et al, 2020), satellite RNAs were found to be commonly associated with the genomes of TBRV and BRSV. The study by Zarzyńska‐Nowak et al (2020) working on TBRV isolated in Poland identified satellite RNAs in 8 of 10 isolates from a range of different plant species, finding them to be associated rather commonly.…”
Section: Discussionsupporting
confidence: 54%
“…The genome structure consists of two linear single‐stranded positive‐sense RNAs: RNA1 and RNA2. Both RNAs show some flexibility in size (depending on particular isolates), with approximately 7,400 and 4,500 nucleotides (nt) for RNA1 and RNA2, respectively (Zarzyńska‐Nowak et al, 2020). The TBRV genome contains two open reading frames (ORFs, one per RNA strand) surrounded by 5′ and 3′ untranslated regions (UTRs) with the small VPg protein attached at the 5′ end and a poly(A) tail at the 3′ end of the RNA molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research indicated that ORF1 (RNA1) encodes mostly nonstructural peptides responsible for virus replication and genome expression, whereas ORF2 (RNA2) encodes structural proteins involved in virion formation and movement (Digiaro et al, 2015). For some of the TBRV isolates, the presence of additional, subgenomic particles like satellite RNAs (satRNA) or defective RNAs (D RNA) has been observed (Budzyńska et al, 2020; Hasiów‐Jaroszewska et al, 2012, 2018; Rymelska et al, 2013; Zarzyńska‐Nowak et al, 2020). These particles are relatively short, noninfectious and their replication, encapsidation, and spread depend on the helper virus.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations